2010
DOI: 10.1007/s11886-010-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Therapy in Acute Coronary Syndrome: How Far Up the Coagulation Cascade Will We Go?

Abstract: The contribution of thrombosis to the natural history and clinical expression of advanced atherosclerotic coronary artery disease is well established. Less well understood is the biochemical and pathobiological distinction between normal hemostasis and thrombosis as the proximate cause of acute coronary syndrome. In this article, we summarize an evolving area of interest within the field of antithrombotic therapy--the contact system and the intrinsic pathway of coagulation, focusing our discussion on factors X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…(With kind permission from Springer+Business Media: Ref. [68], Figure 1.) HMK, high molecular weight kininogen; PL, phospholipid vesicles; PK, pre‐kallikrein; TF, tissue factor; VWF, von Willebrand factor.…”
Section: The Cellular Basis Of Hemostasismentioning
confidence: 99%
“…(With kind permission from Springer+Business Media: Ref. [68], Figure 1.) HMK, high molecular weight kininogen; PL, phospholipid vesicles; PK, pre‐kallikrein; TF, tissue factor; VWF, von Willebrand factor.…”
Section: The Cellular Basis Of Hemostasismentioning
confidence: 99%
“…Similarly, molecular genetic studies in FIX-deficient mice showed a correlation between in vivo FIXa activity and susceptibility to occlusive venous thrombus formation [ 91 ]. In humans, elevated levels of FIX, FXI, or FXII are all associated with prothrombotic phenotypes [ 92 ].…”
Section: Anticoagulation In Acsmentioning
confidence: 99%